Estimation of ulna length as a predictor of height in Nepalese male adult population - Sah, Rajendra Prasad; Rana, Gopal; Bhaskar, Ravi Kumar (Journal of Chitwan Medical College, 2018)
Introduction: Stature estimation from the skeletal remains bears immense importance for the anatomist, anthropologist for the forensic experts. It is conventionally used long bones, the humerus, femur, tibia, etc. Ulna has also been used for the said purpose since 1952. An attempt was made to formulate a linear regression equation for the estimation of the stature of living adult population from the lengths of their ulna. Methods: This study was conducted in the M.B. Kedia Dental College Birgunj from January 2017 to December 2017and participants were chosen from among the patients and their attendants in the OPD. The height was measured from the crown to the heel and the length of the ulna was measured from the tip of the olecranon process to the tip of the styloid process. The documented data was calculated by the standard statistical software. Results: The parameters were tabulated and statistically analyzed. The correlation coefficient (r) was found to be 0.399 (p<0.001) for the left ulna with stature and it was 0.486 (p<0.001) for the right ulna with stature. Supportive regression equations and scatter-plot diagrams could successfully interpret the height from the ulna length of the adult male population. Conclusion: The ulna being almost a percutaneous bone, it can be used for the prediction of the height. The ulna length provides an accurate and reliable means in estimating the height of an individual. The regression formulae which were proposed in this study will be useful for clinicians, anatomists, archeologists, anthropologists and forensic scientists when such evidence provides the investigator the only opportunity to gauge that aspect of an individual’s physical description.